Reparo ósseo de defeitos cirúrgicos críticos preenchidos ou não com ß – fosfato tricálcio (RTR® – Septodont): estudo histológico e histométrico em tíbias de ratos - Guimarães, Maria Rosa Felix de Sousa Gomide [UNESP] (2016)
Objectives: To analyze histologically and histometrically the effect of RTR® on critical surgical bone defects in rat tibiae in the bone repair process. Materials and Methods: Critical bone defects were created in the tibia of 32 Wistar rats divided into two groups: Clot Group and RTR® Group. After the experimental period of 30 and 90 days, the animals were sacrificed and the paraffin embedded pieces were cut and stained with hematoxylin and eosin. Two parameters were analyzed: total neoformed bone area (AON) and bone area of neoformed cortical (ACN). Statistical analysis was performed in the two observation periods by analysis of variance (ANOVA) and Tukey's test. Results: All groups demonstrated superior bone repair when compared to the Clot Group 30 days in the two analyzed parameters. The RTR® Group, in 30 and 90 days, presented repair of the cortical bone and bone tissue formations in the central region of the defect greater than in the 90-day Clot Group, which presented partial repair of the cortical bone and few bone tissue formations in the region of the defect (p <0.05). Conclusions: The RTR® favored the bone neoformation in the adopted experimental model and can be indicated in cases of bone of critical size.